The value of conventional ultrasound combined with superb microvascular imaging and color Doppler flow imaging in the diagnosis of thyroid malignant nodules: a systematic review and meta-analysis - Jiang, Li; Zhang, Dian; Chen, Yue-Nan; Yu, Xue-Juan; Pan, Mei-Fang; Lian, Lian (Frontiers in Endocrinology, 2023)
Purpose: To evaluate and compare the value of conventional ultrasound based superb microvascular imaging (SMI) and color Doppler flow imaging (CDFI) in the diagnosis of malignant thyroid nodule by meta-analysis. Methods: The literature included in the Cochrane Library, PubMed, and Embase were searched by using " superb microvascular imaging (SMI), color Doppler flow imaging (CDFI), ultrasound, thyroid nodules" as the keywords from inception through February 1, 2023. According to the inclusion and exclusion criteria, the clinical studies using SMI and CDFI to diagnose thyroid nodules were selected, and histopathology of thyroid nodules was used as reference standards. The diagnostic accuracy research quality assessment tool (QUADAS-2) was used to evaluate the quality of included literature, and the Review Manager 5.4 was used to make the quality evaluation chart. The heterogeneity test was performed on the literature that met the requirements, the combined sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio were pooled, and a comprehensive ROC curve analysis was performed. Meta-DiSc version 1.4, StataSE 12 and Review Manager 5.4 software were used. Results: Finally, 13 studies that met all inclusion criteria were included in this meta-analysis. A total of 815 thyroid malignant nodules were assessed. All thyroid nodules were histologically confirmed after SMI or CDFI. The combined sensitivity, specificity, PLR, NLR, DOR, and area under the SROC curve of SMI for the diagnose of malignant thyroid nodules were 0.80(95%CI: 0.77-0.83), 0.79(95%CI: 0.77-0.82), 4.37(95%CI: 3.0-6.36), 0.23(95%CI: 0.15-0.35), 22.29(95%CI: 12.18-40.78), and 0.8944, respectively; the corresponding values of CDFI were 0.62(95%CI: 0.57-0.67), 0.81(95%CI: 0.78-0.85), 3.33(95%CI: 2.18-5.07), 0.41(95%CI: 0.27-0.64), 8.93(95%CI: 3.96-20.16), and 0.8498. Deek funnel pattern showed no significant publication bias. Conclusion: The diagnostic efficiency of SMI for malignant thyroid nodules is better than CDFI, and SMI technology can provide significantly more information on vascularity, make up for the deficiency of CDFI, and has better clinical application value.